Synthesis of 1,3-Disubstituted Azetidines via a Tandem Ring-Opening Ring-Closing Procedure - March-Cortijos, Andrea; Snape, Timothy J.; Turner, Nicholas J. (Synlett, 2012)
The synthesis of N-substituted symmetrical azetidines has been achieved in high yields via the reaction of primary amines undergoing an epoxide ring-opening reaction followed by an in situ ring-closing step.
Keywords: azetidines; tertiary alcohols; azo compounds; cyclization; tandem reaction